Implementing Relational Database For Online Ordering Books System - Norfiza, Ibrahim (2002)

(untitled)
The study was carried out in order to produce a Web-based application of Implementing Relational Database for Online Ordering Books System (CoSIS) in Universiti Utara Malaysia (UUM)'s co-operative. This is done due to lack of online systems that can cater for such as ordering books system. The System Development Research Methodology is the methodology used in the study. The prototype of CoSIS is built using the MySQL relational database, together with PHP and Apache Web server. The benefits of these technologies are discussed in this paper. The combination of these technologies makes the CoSIS featured with many benefits that are believed can enhance today's online ordering books system.